The Effect Of Using Kamishibai Through Interactive Strategy On Students’ Ability In Listening Narrative Text - Puput Afrianti (Universitas Muhammadiyah Sumatera Utara, 2022)
The objective of this research was to find out the effect of using Kamishibai through interactive strategy on students’ ability in listening narrative text. This was an experimental research which conducted at SMP Asuhan Jaya Medan at Jalan Kayu Putih Kelurahan Tanjung Hilir, Tanjung Mulia Hilir, Kecamatan Medan Deli, Kota Medan Provinsi Sumatera Utara. The population of this research was the students of grade VIIIth in the academic year 2019/2020 which consisted of 44 students and distributed into 2 (two) classes. By using total sampling technique, 2 classes were chosen as the sample, VIII-1 as the experimental group and VIII-2 as the control group. The experimental group was taught by using Kamishibai through interactive strategy and the control group was taught by using conventional method. In order to collect the data multiple choice test consisting of 20 items were administrated to the student. The result showed that the t-test was greater than t-table (2.1361.683), at